FACTORS ASSOCIATED WITH ACUTE DIARRHOEA AMONG ROTAVIRUS VACCINATED CHILDREN AGED 11-23 MONTHS IN KISUMU EAST SUB-COUNTY - Ochogo, Jane; Arudo, John; Sakwa, Gregory (Journal of Health, Medicine and Nursing, 2022)
Purpose: To investigate the relationship between behavioral factors and acute diarrhea among rotavirus vaccinated children aged 11-23 months in Kisumu East sub-County Materials and Methods: An observational cross-sectional sample design was used to carry out a study in Kisumu East Sub-County. Data was collected by trained field workers and community health volunteers who were residents of the 3 identified sub locations in Kisumu East Sub- County that was Nyalenda A, Manyatta B and Kolwa Central which included Nyalunya and Kasule. For quantitative results Multivariate logistic regression analysis was used to determine association between behavioral factors and acute diarrhea among rotavirus vaccinated aged 11-23 months in Kisumu East Sub-County. Data on Participants regarding behavioral factors influencing acute diarrhea among rotavirus vaccinated children aged 11-23 months in Kisumu East Sub-County, were collected with structured questions using Stata version 14 computer software. Data entry analysis was performed. Logistic regression analysis was conducted and the odds ratio was used in Kisumu East Sub-County to assess the relationship between behavioral factors and acute diarrhea among rotavirus vaccinated children aged 11-23 months. The multivariate analysis considered all variables with P values <0.05 was used to establish statistical significance. Findings: Bivariate analysis on behavioral factors and caregiver practices influencing diarrhea in children. Having soap for hand washing (OR: 20; 95% CI: 1.2 -3.4 p = 0.008), having piped water as the main source of drinking water ( OR: 2.6, 95% CI: 1.5 - 4.6; p = 0.0006 ), using pit without slab where child's feaces are disposed were all associated with increased likelihood of cases of diarrhea among children (OR: 2.6; 95% CI: 1.2 -5.4; p= 0.01). It is worth noting that respondents who had pot without tap for water storage were upto 14.5 times more likely to have reported their children having diarrhea, the result however not statistically significant (p = 0.09). The chances of children presenting with diarrhea in the past 14 days prior to the survey was likely in the following situations: Washed hands after handling child's feaces, napkins or diapers, (OR: 0.6; 95% CI: 0.4 -1.0; p= 0.030) or washing hands after visiting toilet/before preparing food or drink/before meals/after handling child`s feaces, napkins or diapers (OR: 0.4; 95% CI: 0.2 - 0.9; p= 0.02). Equally, of caregivers whose main source of water was lake (OR: 0.3 95% CI: 0.1- 1.0; p= 0.04 ) , those who were using filtration or not treating their water to make it safe ( OR: 0.2; 95% CI; 0.1 -0.8 p= 0.01 ), or respondents who were using flush toilet to dispose the child`s feaces ( OR: 0.2 ; 95% CI: 0.3- 0.9; p=0.02 ) , all with statistically significant results. Unique contribution to theory practices and policy: Socio-economic factors, environmental and behavioral factors and knowledge factors all influence acute diarrhea among rotavirus vaccinated children aged 11-23 months in Kisumu East sub-County. The relevant stakeholders should enlighten and educate the parents/guardians of the children on the factors associated with diarrhea among rotavirus vaccinated children aged 11-23 months in Kisumu East sub-County.